Komparasi Sistem Pendukung Keputusan Performa Kementerian Agama Menggunakan Metode Kombinasi Fuzzy Logic Mamdani Dan Sugeno - Abdul Hamid; Abdul Syukur; Arief Sulaiman; Supriyanto (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2026)
Performance evaluation of the Regency/City Offices of the Ministry of Religious Affairs within the Regional Office of the Ministry of Religious Affairs of Central Java Province is an important process that must be conducted objectively and measurably. Common issues in performance assessment include the large number of evaluation criteria, uncertainty in performance values, and the tendency toward subjectivity in the evaluation process. This study aims to compare the performance of Fuzzy Logic Mamdani and Fuzzy Logic Sugeno methods in determining the performance level of the Ministry of Religious Affairs. The data used in this study are secondary data obtained from performance evaluation reports of 35 Regency/City Offices of the Ministry of Religious Affairs, using five criteria: performance planning, performance measurement, performance reporting, internal evaluation, and performance achievement and accountability. The implementation of the fuzzy inference system was carried out using MATLAB with the Fuzzy Logic Toolbox. The results of data processing indicate that the obtained performance achievement score is 50%, which falls into the “Fair” category, indicating that the work units have a reasonably good level of performance accountability but still require improvements. The comparative analysis shows that both the Mamdani and Sugeno methods produce the same performance values and categories, indicating that both methods can be accurately applied as decision support systems in determining the performance level of the Ministry of Religious Affairs objectively.